Australia : 2009 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion;. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that following a prolonged expansion, reflecting sound macroeconomic policies and favorable terms of trade, global events have slowed Australia's economic growth well below trend. The turmoil sparked by the collapse of Lehman Brothers in September 2008 had an immediate impact on Australian markets. Executive Directors have commended the authorities for their timely policy response, which has effectively cushioned the impact of the global financial crisis on the Australian economy. Directors have also welcomed the Reserve Bank of Australia's early reductions in the policy rate.